Influence of basal melting on ice surface fracture and glacier retreat: A case study at Pine Island Glacier - Boya Yan; Baojun Zhang; Pei Jiang; Qian Li; Yunsi Wu; Mingliang Liu (Polish Polar Research, 2025)
Pine Island Glacier (PIG) is one of the most dynamic ice streams in West Antarctica, with significant basal melting and ice shelf retreat profoundly influencing its behavior. In this study, through remote sensing imagery and ice flow velocity data, we identified two major retreats of the PIG ice shelf in 2015 and 2018, and notable fluctuations in the ice flow velocities of PIG ice flow from 2013 to 2018. Analysis of CryoSat-2 data revealed that the annual average basal melt rate of the ice shelf peaked at ~14±0.8 m yr–1 in 2016. We conducted simulations using an ice flow model to assess the effects of ice shelf retreat and basal melting. The results showed that the significant acceleration of ice flow on PIG in 2018 was due to the removal of the compressive arch during the 2018 ice shelf retreat, causing large dynamic changes. The deceleration in 2016 was attributed to substantial basal melting, which reduced the longitudinal force and weakened the ice shelf’s buttressing force, leading to an acceleration in 2017. Furthermore, extensive basal melting promoted the development of surface fractures on the southern side of the main ice shelf, contributing to the significant retreat observed in 2018. Consequently, a “melting-fracture-collapse-acceleration” process has been identified, which is supposed to occur in ice shelves with significant basal melting. A sudden decrease in the surface flow velocity of an ice shelf may serve as an early warning for an accelerated rate of mass loss in the ice shelf system.